Analisis Semiotika ANALISIS FILM “YOU ARE THE APPLE OF MY EYE” MENGGUNAKAN TEORI DARI ROLAND BARTHES: Analisis Semiotika Menggunakan Teori Roland Barthes - Pandu Pandu Maulana; Sabri (STISIP Widyapuri Mandiri Sukabumi, 2023)
According Susanto, 1982: 60 film is the delivery of messages through moving images, utilizing camera technology, color and sound. These elements are based on a plot that contains the message that the director wants to convey to the audience. The plot of this movie revolves around Ko Ching-teng, a very naughty and cheerful high school student who is more interested in playing around and than studying. His character changes when a new transfer student named Shen Chia-yi enters his class. Ching-teng is immediately smitten by Chia-yi's beauty and intelligence. The storyline in this movie is very similar to teenage romance stories. This research uses the semiotic theory of Roland Barthes. The data collection technique used by the author is to watch the original movie from beginning to end, while observing or paying attention to each scene, making observations related to the movie. This research uses qualitative research methodology using content analysis method.